Experimental study on toxicity of Indian major carp bile - S. Munilkumar; J.K. Sundaray; K. Venkateshvaran; Rida Riyaz (Journal of Indian Fisheries Association, 2024)
Raw bile of three Indian Major Carps viz., Catla catla, Labeo rohita, and Cirrhina mrigala was screened for their ichthyohepatotoxic properties. The raw bile of all the three species exhibited spontaneous haemolysis of sheep blood. Fish bioassay was conducted by intraperitoneal administration of raw bile to the test fish Labeo rohita of 30±5 g weight. Raw bile of all the three species studied proved to be toxic to the fish with Median Survival Time of 14 hours at 0.03 cc, 14 hours at 0.05 cc, and 18 hours at 0.05 cc of the bile of Catla, Rohu and Mrigal respectively. Behavioral and other changes included external inflammation of belly region, necrosis at the site of injection, piping, lethargy, vertical orientation, general apathy and lack of responsiveness, abdominal dropsy, and visceral hemorrhage. The results indicate Catla bile to be the most toxic followed in decreasing order by Rohu and Mrigal bile. The results are discussed in light of earlier published data and the potential risks of acute renal damage for human beings are indicated.